Penerapan Culturally Responsive Teaching Dalam Pembelajaran Surat Pribadi dan Surat Dinas Berbasis Budaya Lahan Basah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe how the Culturally Responsive Teaching approach is implemented in the teaching of personal letters and official letters by using wetland culture as the local context in Grade VII of SMPN 1 Banjarmasin. Through this approach, the learning materials are connected to the cultural environment of the students, such as activities in floating markets, life in floating houses, and the traditions of river communities. This research uses a descriptive qualitative method with content analysis applied to the Indonesian language learning module. The findings show that the five main dimensions of Culturally Responsive Teaching, namely Content Integration, Facilitating Knowledge Construction, Prejudice Reduction, Social Justice, and Academic Development, are applied successfully and create learning that is relevant, enjoyable, and able to encourage active student participation. The module provides opportunities for students to express their personal experiences and cultural background through writing personal letters and official letters. Besides improving writing skills, this approach also helps build cultural awareness and character development. Therefore, Culturally Responsive Teaching has strong potential to be applied more widely in the development of learning materials based on local wisdom.